Pengembangan Kreativitas Kelompok Pembinaan Kesejahteraan Keluarga (PKK) Pada Kegiatan Peta Kaca Melalui Pembuatan Tas Kain Perca - Anwar, A Khoirul; Amarta Reszky, Ayudiya; Putri, Egia; Azzahra, Izah (Jurnal Etnik: Ekonomi-Teknik, 2022)
Garbage or waste is one of the problems that is always a concern. Used goods, garbage, and household waste can be useful items if they can be processed into unique and useful handicrafts. Household waste such as used wood, used cans and leftover patchwork can be a choice of materials that can be processed. The purpose of this community service activity is to provide skills in utilizing patchwork into handicrafts in the form of bags, to the PKK group in Buaran Village, South Tangerang City. The method used in this PKM activity is community empowerment which is pursued through socialization with several implementation preparations, namely (1) Describing the use of patchwork waste as a creative product (2) The practice of making patchwork bags. The result of this activity is the provision of skills in waste processing in the form of patchwork, so that it can reduce environmental pollution and help the community in increasing income during the Covid-19 pandemic which results in the death of the economy in the community.